2010
DOI: 10.5296/jmr.v3i1.487
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stressful Work, Citizenship Behaviour and Intention to Leave the Organization in a High Turnover Environment: Examining the Mediating Role of Job Satisfaction

Abstract: This study investigates the extent to which job satisfaction mediates the relationship between job stress work outcomes, such as intention to leave the employer and citizenship behaviour (OCB). Job satisfaction is examined as a mediator between stress and intention to leave, and OCB. The procedure advocated by Baron and Kenny (1986) was selected for the mediation test. The result pattern across both samples was very similar. While no relationship was found between stressful work and OCB, stressful work increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 62 publications
6
47
1
9
Order By: Relevance
“…On the other hand, employees will quit the organization if they have low organizational commitment, this finding concurrent with past studies by Anvari and Amin (2011), Abu Elanain (2010), Elangovan (2001), Lambert (2006), Paille (2011), Perryer et al (2010), and Yong-Tao (2007. This finding can be explained by the cognitive consistency theory that states that an individual will attempt to maintain harmony between his or her behaviors, belief, and attitude.…”
Section: Organizational Commitment and Turnover Intentionsupporting
confidence: 79%
See 2 more Smart Citations
“…On the other hand, employees will quit the organization if they have low organizational commitment, this finding concurrent with past studies by Anvari and Amin (2011), Abu Elanain (2010), Elangovan (2001), Lambert (2006), Paille (2011), Perryer et al (2010), and Yong-Tao (2007. This finding can be explained by the cognitive consistency theory that states that an individual will attempt to maintain harmony between his or her behaviors, belief, and attitude.…”
Section: Organizational Commitment and Turnover Intentionsupporting
confidence: 79%
“…On a similar terms, organizational commitment is described by Porter et al (1974) as consisting having a minimum of three tenets, first, the strong agreement and belief in the goals and values of the organization's , second, the inclination to employ substantial effort to benefit the organization; and three, demonstrating the desire to maintain in the organization. Furthermore, Jaros (1997) and Paille (2011) suggested that organization leaders particularly value high organizational commitment among their employees. Kumar et al (2012) also claimed that employees' commitment can minimize turnover intention, and organizations with high level of employees' commitment will be able to efficiently and effectively achieve their goals.…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction on job had a positive relationship with OCB but it played a strong negative role on employees' intention to leave. It was revealed that employee who is satisfied with his/her job can easily cope with his/her stressful work due to the environment provided at his/her working environment (Paillé, 2011). Stress can have both positive and negative effect; positive effect can be motivating whereas negative effect can lead to different physical and psychological problems through distress, rejection and depression (Mehta & Singh, 2014).It was revealed that 36 % Nepalese nurses cited lack of opportunity to discuss problems with peers as a low source of stress whereas 30% cited inadequate emotional preparation, 24% cited sexual harassment,20% cited discrimination because of race or ethnicity and 10% cited gender based discrimination (Ahsan, Abdullah, Fie, & Alam, 2009).…”
Section: Correlation Between the Occupational Role Stress And Mental mentioning
confidence: 99%
“…We thus respond to calls to apply contingency approaches to study POP outcomes (Bouckenooghe, 2012;Chang, Rosen, Siemieniec, & Johnson, 2012;Lee & Peccei, 2011;Miller, Rutherford, & Kolodinsky, 2008) and demands for studies to clarify how stress-inducing work conditions turn employees away from OCB (Eatough et al, 2011;Noblet et al, 2006;Paillé, 2011). We posit that employees' negative reactions to politicized organizational environments, in the form of reduced OCB, may be attenuated by two types of resources: those embedded in the organizational context (transformational leadership and knowledge sharing) and the personal ability to bounce back and learn from adverse work situations.…”
Section: Introductionmentioning
confidence: 99%